IMPROVING SCIENCE LEARNING ACTIVITIES AND OUTCOMES USING AN "INTERNAL" LEARNING MODEL - Fathul Jannah; Raihanah Sari; Yogi Prihandoko; Yogo Dwi Prasetyo; Sonia Indriati (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
The problem in this study is the low activity and student learning outcomes in learning natural sciences. The INTERNAL model integrates Inquiry, Number Head Together, and snowball throwing. This study uses a qualitative approach and the type of classroom action research (CAR), which was held for four meetings. Data analysis in the form of teacher activity sheets, student activity sheets, and student learning outcomes sheets. Data collection techniques in the form of observation and writing tests. The study subjects were the fifth-grade students of SDN Swato 2 Tapin for the academic year 2021/2022, a total of 32 students. The activity success indicator scores 58-72, and student learning outcomes with minimum standards <70 with classical>80%. The study results indicate that the teacher's activity at the first meeting scored 54 with the "Good" criteria, increasing at the fourth meeting with a score of 74 with the "Verry Good" criteria. Student activity classically at the first meeting reached 25" on the "Very Active" criteria, increased at the fourth meeting to 83,3% with the "Very Activity" criteria. Student learning outcomes at the first meeting with 50% classical completeness increased at the fourth meeting with 100% classical completeness. It can be concluded that applying the internal learning model can improve student activities and learning outcomes.